The Nexus between Government Intervention and Economic Uncertainty During the COVID-19 Pandemic - RABHI, Ayoub; HAOUDI, Amina; TOUATI, Ali Bennagem (Journal of Advanced Studies in Finance; Vol 12 No 1 (2021): JASF Volume XII Issue 1(23) Summer 2021DO - 10.14505//jasf.v12.1(23).07, 2021)
The COVID-19 pandemic urged governments around the world to intervene and respond with different measures aiming to contain the spread of the virus and mitigate the global economic impact, nevertheless, uncertainty skyrocketed and dominated the world economy. In this paper, we examine the relationship between government intervention and economic uncertainty amid the COVID-19 pandemic. Using monthly data from January 2020 to September 2020 from 22 countries, we found that economic uncertainty during the first nine months of the pandemic reacted more to government intervention than to the number of COVID-19 cases, we also found that the response to face the pandemic had also different effects on economic uncertainty depending on the type of actions, since the containment policies increased economic uncertainty while the economic support to households’ action decreased it. Our results show that government intervention in different countries around the world had both positive and negative impacts on economic uncertainty and this has an important conclusion about government intervention effects on the economy during the COVID-19 pandemic.